Complications after Primary Total Hip Arthroplasty : A Comprehensive Clinical Guide - Abdel, Matthew P.; Della Valle, Craig J. (Springer International Publishing : Imprint: Springer, 2017)
Covering both acute post-operative and chronic complications following total hip arthroplasty (THA), this comprehensive clinical guide provides diagnostic and management strategies and techniques for orthopedic surgeons at every level. Utilizing a case-based approach, each condition is discussed in terms of its epidemiology, risk factors, and preventative measures, with a brief literature review providing evidence for the diagnosis and treatment each author selects. The first section covers acute post-operative complications, discussing peripheral nerve and vascular injuries, periprosthetic fractures and infections as well as thromboembolic events. The second section covers chronic complications including the more common complications such as recurrent dislocation and infection as well as rarer complications such as pelvic discontinuity. Aimed at the most efficient management of these often complicated conditions, Complications after Primary Total Hip Arthroplasty is a practical resource for orthopedic surgeons, residents and fellows working with patients having undergone hip replacement surgery.
Keywords: Medicine.; Orthopedics.; elektronické knihy; electronic books